2017
DOI: 10.1037/xge0000363
|View full text |Cite
|
Sign up to set email alerts
|

Threat of shock and aversive inhibition: Induced anxiety modulates Pavlovian-instrumental interactions.

Abstract: Anxiety can be an adaptive response to potentially threatening situations. However, if experienced in inappropriate contexts, it can also lead to pathological and maladaptive anxiety disorders. Experimentally, anxiety can be induced in healthy individuals using the threat of shock (ToS) paradigm. Accumulating work with this paradigm suggests that anxiety promotes harm–avoidant mechanisms through enhanced inhibitory control. However, the specific cognitive mechanisms underlying anxiety-linked inhibitory control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(39 citation statements)
references
References 48 publications
4
35
0
Order By: Relevance
“…Across studies, we replicated a previous finding that threat of shock slows down reaction times to target ‘go’ stimuli [9,13,24]. We suggest an explanation for this, where being cautious when under threat of shock prevents impulsive responding, and reduces the risk of harmful behaviour.…”
Section: Resultssupporting
confidence: 85%
“…Across studies, we replicated a previous finding that threat of shock slows down reaction times to target ‘go’ stimuli [9,13,24]. We suggest an explanation for this, where being cautious when under threat of shock prevents impulsive responding, and reduces the risk of harmful behaviour.…”
Section: Resultssupporting
confidence: 85%
“…As a manipulation check, participants retrospectively rated how anxious they felt during the safe and threat conditions on a scale from 1 (“not at all”) to 10 (“very much so”). This well-established12 manipulation has been shown to have high reliability19 and replicability28. There were four threat and four safe conditions, each involving 50 trials and lasting ~5 minutes each.…”
Section: Methodsmentioning
confidence: 99%
“…For example, people with schizophrenia exhibit reinforcement learning deficits with an associated reduction in the Go bias 23 . On the other hand, traumatic stress is associated with increased Pavlovian biases 24 while anxiety is specifically associated with increased avoidance bias in the face of threats 25 . People with depression show similar Pavlovian bias to healthy controls 69 , though interestingly in this study we found an association between avoid-loss bias and BDI.…”
Section: Discussionmentioning
confidence: 99%
“…Under normal circumstances, Pavlovian biases broadly influence adaptative behavior—they guide learning and form the basis for responding rapidly with little cognitive effort. However, they can become maladaptive 3 , 23 25 . People with PD in particular demonstrate difficulty in learning to withhold actions especially for reward outcomes 26 , 27 .…”
Section: Introductionmentioning
confidence: 99%